Bima Kroda's a Study of Text and Context | Bima Kroda sebuah Kajian Teks dan Konteks - Gede Navio Raykin (Pusat Penerbitan LPPMPP ISI Denpasar, 2024)
In Tejakula Village, there is a report on a piece of madness. In the report, there is one gegilakan percussion, namely the Bima Kroda Gegilakan Percussion; this percussion comes from Tejakula Village and through this object, the researcher conducted research analyzing the Bima Kroda Gegilakan Percussion in terms of text and context. The entire research process was carried out using Ari Kunto's research and application methods and the data collection techniques of observation, interviews, documentation, literature study, and discography. The Bima Kroda Gegilakan Percussion is a gegilaan percussion included in the repertory of gegilakan music in Tejakula Village. The appearance of this percussion is estimated to be in the 1925s, and the creator of this percussion is unknown. Bima Kroda's Gegilakan Percussion contains musical and extra-musical elements. The musical elements consist of 1) tone, using 5-tone pelog tunings; 2) rhythm, using symmetrical rhythm; 3) time signature, using 4/4 time signature; 4) Tempo, using a fast and steady tempo; 5) dynamics, experiencing changes in the dynamics of crescendo and decrescendo. Meanwhile, the extra-musical element can be seen through the philosophy of the name of the percussion itself. The uniqueness of this percussion is that it has its charm. It is said that when this percussion is performed in temples or at art performances, it can invite enthusiastic audiences to give appreciation.